A PERSPECTIVE STUDY ON AQUA CULTURE’S PROBLEMS AMONG COASTAL ANDHRA - Raju, M L N (IJRDO - Journal of Applied Management Science, 2016)
Aquaculture has been a fast-growing industry because of significant increases in demand for fish and seafood throughout the world. Aquaculture plays a significant role in the development of the country economy as well as state economy Coastal environment has undergone rapid change in recent times. Change in the state of the environment is multifaceted, but a key concern is the way that natural habitats the coastal zone is characterized by ambiguities of resource ownership and a complex web of interactions among people, resources and ecosystems. Conflicts exist between the needs of people who may gain from intensification of land use for agriculture and or aquaculture and other people who are Livelihoods may be adversely affected by environmental impacts. Mainly Fish were exposed to any toxicant of different concentrations, due to stress the physiology gets disturbed, thus considerably affects so in this research paper represent the facing various environmental Problems and approaches to managing change in the inland coastal zone in Andhra Pradesh.